PENGARUH KOMPENSASI DAN PENGALAMAN KERJA TERHADAP KINERJA PEGAWAI ASN PADA SATPOL PP DAN DAMKAR - Tanti Harlena; Eska Prima Monique; Siti Hanila (STIA Bengkulu, 2023)
The purpose of this study is to prove that compensation and work experience have an effect on the performance of ASN employees at Satpol PP and Firefighters. The researcher took the sample by accidental sampling and chose several people who were considered to represent the population, totaling 42 ASN employees. The magnitude of the coefficient of determination from the calculation results using SPSS can be seen that the coefficient of determination from R square is 0.570. This means that the value of compensation (X1) and the value of work experience (X2) affect employee performance (Y) by 57.0% while the remaining 43.0% is influenced by other variables not examined in this study. The results of the t-test at a significance level of 0.05 explain that partially compensation and work experience have a significant influence on the performance of employees at Satpol PP and Damkar in South Bengkulu Regency. The results of the f test at a significance level of 0.05 explain that compensation and work experience have a significant simultaneous influence on employee performance at the Satpol PP and Damkar South Bengkulu Regency